Caries arrest and lesion appearance using two different silver fluoride therapies with and without potassium iodide: 6-month results. Issue 7 (July 2020) - Turton, Bathsheba; Horn, Rithvitou; Durward, Callum
Abstract: Objectives: to compare arrest rates and colour change in carious lesions in primary teeth using two different silver fluoride solutions with and without potassium iodide (KI). Methods: The study was a four-armed, parallel-design randomised controlled trial and investigated four protocols for caries arrest at 6m. Children in Group 1 and Group 2 received Rivastar Silver Diammine Fluoride (SDF), and Children in Group 3 and Group 4 received an aqueous silver fluoride solution (AgF). Children in Group 2 and Group 4 received a two-step procedure where application of the AgF or SDF solution was followed by KI. Results: At the six-month follow-up 446 (82.2%) children were re-examined. The arrest rate across the full sample was 51.4% and there were no significant differences in arrest rate by type of silver fluoride therapy. The lesion size, tooth type, surface type, presence of plaque on the carious lesion and caries increment all had an influence on caries arrest. Once clustering effects were accounted for, the use of KI was associated with a higher chance of arrest (OR 1.23; P-value 0.008) and a lower chance of the lesion darkening (OR 0.73; P-value <0.001). Conclusions: The combination of AgF & KI was associated with the most favourable clinical outcomes in terms of caries arrest and lesion colour. Clinical significance: The major draw-back of arrest of caries treatment with silver fluoride solutions is that it can create an appearance which may be aesthetically unacceptable. This study explores ways in which the base colour of lesions could be improved and as such provide the opportunity for better aesthetic outcomes for children afflicted with a severe burden of dental caries in their primary dentition, and in whom conventional treatment is not being provided. Abstract : Public Health; Epidemiology; Dentistry; Dental Materials; Pediatrics; Evidence-Based Medicine; Clinical Research; Dental Caries, Aesthetics, Caries arrest, Cambodia, Silver Fluoride